Un nuevo paradigma para una nueva era - Cardero López, José Luis; Ibáñez, Alberto G. (Nómadas. Critical Journal of Social and Juridical Sciences, 2006)
We are living several events and discoveries that are menacing our traditional vision of reality and knowledge. Therefore, it is quite important to prepare our mind and our capacity of analysis in order to respond adequately to new threats. It is not only a question of accepting once more a change of paradigm, but rather to change our common way of thinking. In fact, scientific approach is only useful to embrace a small portion of reality, that suitable to be measured. That is the reason why such an approach needs to be complemented by others. This article argues that a new pending model must accept that knowledge is featured by dynamism and movement, and must be applicable to all kind of questions whether they are considered by society legitimate or illegitimate.